Expert Evaluation of Diagnostic Instrument for Personal and Organizational Value Congruence - Vveinhardt, Jolita (Journal of business ethics, 2016)
The article aims to evaluate the quality of a newly constructed diagnostic instrument for personal and organizational value congruence. To attain this, an expert evaluation was invoked. The selected experts evaluated the questionnaire scales and their constituent subscales as well as the eligibility of the contained statements for diagnosing of personal and organizational value congruence. It should be emphasized that the experts were provided a possibility of commenting on each of the statements, making observations and providing suggestions in regard to the statements, scales and subscales of the questionnaire. This article presents the analysis of the evaluation commentaries by the experts, basing on which the main drawbacks of the new instrument were identified and highlighted. Furthermore, a new diagnostic instrument, constructed in accordance with the results of the expert evaluation as applicable for personal and organizational value congruence is introduced as the main result of the research.